2019
DOI: 10.1126/science.aau1043
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing mutagenic effects of recombination through a sequence-level genetic map

Abstract: Genetic diversity arises from recombination and de novo mutation (DNM). Using a combination of microarray genotype and whole-genome sequence data on parent-child pairs, we identified 4,531,535 crossover recombinations and 200,435 DNMs. The resulting genetic map has a resolution of 682 base pairs. Crossovers exhibit a mutagenic effect, with overrepresentation of DNMs within 1 kilobase of crossovers in males and females. In females, a higher mutation rate is observed up to 40 kilobases from crossovers, particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
458
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(496 citation statements)
references
References 113 publications
32
458
2
4
Order By: Relevance
“…Inter-individual variation in crossover rates has previously been visible through computational analyses of SNP data [1][2][3][4][5][6][7][8][9][10] . Here, single-gamete sequencing revealed that donors 415 with high crossover rates also exhibit other meiotic phenotypes, including a tendency to make crossovers closer together and to place a smaller fraction of their crossovers in telomereproximal zones (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-individual variation in crossover rates has previously been visible through computational analyses of SNP data [1][2][3][4][5][6][7][8][9][10] . Here, single-gamete sequencing revealed that donors 415 with high crossover rates also exhibit other meiotic phenotypes, including a tendency to make crossovers closer together and to place a smaller fraction of their crossovers in telomereproximal zones (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…DNA variation data are now available for millions of people and thousands of families; the locations of crossovers can be estimated from genomic segment sharing among relatives and linkage-disequilibrium patterns in populations [1][2][3][4][5] . Although these studies sample 30 only the small number of reproductively successful gametes from individual humans, such analyses have revealed that average crossover number and crossover location vary among individual humans and associate with common variants (single nucleotide polymorphisms, SNPs) at many genomic loci 4,[6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…It should be appreciated that the correlations between recombination rate, the density of conserved sites and genetic diversity may be an artifact of deficiencies in multiple regression. Recombination is known to be mutagenic in humans (Lercher & Hurst 2002;Hellmann et al 2005;Pratto et al 2014;Francioli et al 2015;Arbeithuber et al 2015;Halldorsson et al 2019) and since d NC is an imperfect measure of the mutation rate, this may allow the rate of recombination to remain significant in a multiple regression. Similarly, there is a negative correlation between the density of conserved sites and our measure of the mutation rate, d NC .…”
Section: Discussionmentioning
confidence: 99%
“…Since the rate of substitution is also correlated to the rate of recombination it seemed likely that at least part of the correlation between diversity and the rate of recombination was due to a mutagenic effect of recombination. There is now good evidence that recombination is mutagenic in humans (Pratto et al 2014;Francioli et al 2015;Arbeithuber et al 2015;Halldorsson et al 2019) and recent analyses of the correlation between diversity and the rate of mutation, as inferred from rates of de novo mutations in human trios, suggests that much, but not all, of the variation in diversity across the human genome can be explained by variation in the rate of mutation at the 100KB and 1MB scale (Smith et al 2018) . However, several lines of evidence suggest that selection at linked sites may also affect neutral and selected diversity across the human genome.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using DMC1 ChIP-Seq data from human spermatocytes, Pratto et al, 2014 observed C>G enrichment to a small degree around male autosomal hotspots (68), but the source of these types was not discussed further by the authors, and is potentially due to overlap with regions of clustered de novo C>G mutations reported by Jónsson et al, 2017. Another recent study did not find de novo C>G mutations enriched within autosomal crossover hotspots identified in pedigree studies (69). We test if there is indeed an enrichment of C>G mutations associated with meiotic DSBs by comparing the mutation spectrum within and outside hotspots on autosomes; we use DMC1 hotspots in males and crossover hotspots in females because we do not have a map of DMC1-binding in female gametes.…”
Section: Accidental and A Subset Of Meiotic Double-strand Breaks In Tmentioning
confidence: 98%